2003
DOI: 10.1002/bem.10071
|View full text |Cite
|
Sign up to set email alerts
|

The effect of strong static magnetic field on lymphocytes

Abstract: We investigated whether static electromagnetic fields (EMFs) at a flux density of 4.75 T, generated by an NMR apparatus (NMRF), could promote movements of Ca2+, cell proliferation, and the eventual production of proinflammatory cytokines in human peripheral blood mononuclear cells (PBMC) as well as in Jurkat cells, after exposure to the field for 1 h. The same study was also performed after activation of cells with 5 mg/ml phytohaemagglutinin (PHA). Our results clearly demonstrate that static NMRF exposure has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 35 publications
(35 reference statements)
2
42
0
Order By: Relevance
“…In a previous report, in which these conditions were similar to those in our present study, an exposure of 4.75 T for up to 48 h had no proliferative, activating, or proinflammatory effects on peripheral blood MNCs. 31 There are possible limitations to this study. First, in this study, the effect of EMF itself on the repair process of injured muscle was not examined.…”
Section: Discussionmentioning
confidence: 92%
“…In a previous report, in which these conditions were similar to those in our present study, an exposure of 4.75 T for up to 48 h had no proliferative, activating, or proinflammatory effects on peripheral blood MNCs. 31 There are possible limitations to this study. First, in this study, the effect of EMF itself on the repair process of injured muscle was not examined.…”
Section: Discussionmentioning
confidence: 92%
“…45 Finally, Aldinucci and colleagues demonstrated that magneticˆelds decrease the levels of interleukin-2 and Ca 2+ in Jurkat cells but did not aŠect concentrations of interleukin-1b, -2, and -6, interferon, and tumor necrosis factor a in normal human lymphocytes. 46 These reports indicate diŠerences between normal and cancer cells in sensitivity to magneticˆelds.…”
Section: Recent Medical Applications That Use Electromagnetic Fieldsmentioning
confidence: 99%
“…It has been shown that static HMF under 5 T has little or no effect on cell growth (1,2). Depending on the cell type, different influences of HMF on apoptosis have been reported (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…Depending on the cell type, different influences of HMF on apoptosis have been reported (3)(4)(5)(6). HMF may also perturb Ca 2ϩ signaling in cells, although this is also dependent on the cell type (1,6,7).…”
mentioning
confidence: 99%